Incidencia y tratamiento de la parasitosis en niños de 2 y 7 años de la ciudadela Los Ceibos, Parroquia Nueva Santa Rosa, del cantón Sta. Rosa año 2004. - Estrada Luna, María L. (2005)
The Parasitosis is all illness taken place by parasites, animal organisms or vegetables that you/they live to other beings expense and that they invade the organism of who it resides as guest and of who they feed. In the man the parasites can be it was and inside the body. This investigation study is centered in those that are evacuated in the grounds.